PRENATAL MASSAGE TERHADAP PENURUNAN TEKANAN DARAH IBU HAMIL DENGAN HIPERTENSI KEHAMILAN DI PMB DINCE SYAFRINA, SST - Rita Afni; Octa Dwienda Ristica (LPPM Universitas Abdurrab, 2022)
ABSTRACT Hypertension in pregnancy is common and can be one of the top three (besides bleeding and infection) internal causes of death. The number of maternal deaths compiled from the recording of family health programs at the Ministry of Health in 2020 shows 4,627 deaths in Indonesia. Management of hypertension in pregnancy can be done with pharmacological therapy and also non-pharmacological therapy, one of which is by doing prenatal massage. Massage therapy has the advantage that it can reduce levels of the stress hormone cortisol, decrease levels of depression and anxiety, reduce the risk of heart attack, kidney failure, and stroke and improve blood flow. Thus, pregnancy massage can be used in therapy to lower blood pressure in pregnant patients. The purpose of this study was to determine the effectiveness of Prenatal Massage on reducing blood pressure of pregnant women with pregnancy hypertension at PMB Dince Syafrina. This type of research is quasi experimental with a one group pretest posttest approach. The sample in this study were pregnant women with hypertension during pregnancy who visited PMB Dince Syafrina from January-April 2022, totaling 35 pregnant women with hypertension. The analysis carried out is univariate and bivariate analysis. The results showed that the average pre-systolic blood pressure value for pregnant women was 136.03 mmHg with a standard deviation of 9,083and the average post-systolic blood pressure for pregnant women was 130.94 mmHg with a standard deviation of 8,775 while the average diastolic blood pressure value for pregnant women was pregnant women is 90.77 mmHg with a standard deviation of 6,399 and the average post diastolic blood pressure of pregnant women is 85.91 mmHg with a standard deviation of 4,925. Statistical test results show p value 0.001 which means <0.05, it can be concluded that prenatal massage performed on pregnant women with high blood pressure can reduce blood pressure in pregnant women.